2012
DOI: 10.1210/jc.2011-1851
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Celiac Disease as Cause of Increased Need for Thyroxine: A Systematic Study

Abstract: Atypical CD increases the need for T4. The effect was reversed by GFD or by increasing T4 dose. Malabsorption of T4 may provide the opportunity to detect CD that was overlooked until the patients were put under T4 therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
78
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 20 publications
1
78
1
5
Order By: Relevance
“…In the present study, patients with ATD and concomitant CD did not have typical symptoms, which include chronic diarrhea, loss of weight, or anemia, and this can occur in a high percentage of cases (22). Our patients had most commonly gastric distention and heartburn that represent gastrointestinal symptoms seen in the general population.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…In the present study, patients with ATD and concomitant CD did not have typical symptoms, which include chronic diarrhea, loss of weight, or anemia, and this can occur in a high percentage of cases (22). Our patients had most commonly gastric distention and heartburn that represent gastrointestinal symptoms seen in the general population.…”
Section: Discussionmentioning
confidence: 44%
“…This fact can be explained by mucosal damage or presence of undigested food and a net increase of water in the intestinal lumen. Partial recovery of mucosal structure may be sufficient to improve T4 absorption (21,22). In this context, one patient of our study with confirmed diagnosis of CD, which has been treated by the gastroenterology service of our hospital, had a reduction in the dosage of levothyroxine from 175 to 125 mcg, with a better control of the hypothyroidism, approximately one year after the initiation of a GFD.…”
Section: Discussionmentioning
confidence: 94%
“…Exclusion criteria were: i) a history of hyperthyroidism or toxic nodular goitre as well as the presence of autonomously functioning areas in the thyroid scan; ii) the recent use (!6 months) of drugs known to interfere with thyroid homeostasis (20); iii) the presence of concomitant gastrointestinal disorders (gastritis related to Helicobacter pylori infection, atrophic gastritis, coeliac disease, lactose intolerance, etc.) known to increase L-T 4 requirement (21,22,23); iv) being pregnant.…”
Section: Methodsmentioning
confidence: 99%
“…All patients with NTMG were treated with an individually tailored dose of T 4 , as previously described (21,22,23,24) and in semi-suppressive mode (target serum TSHZ0.1-0.5 mU/l) (2). The individually tailored dose is the dose of T 4 which is administered following a standardized assumption procedure and titrated on the basis of patient's age, weight, BMI, the amount of residual thyroid tissue and the ability to absorb the hormone (12,14,15,21,22,23,24).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation